Science Teacher Education in South America: The Case of Argentina, Colombia and Chile - Cofré, Hernán (2015)
In this review, the main characteristics of science teacher education in three countries in South America, namely Argentina, Chile and Colombia, are examined. Although reforms toward constructivist and inquiry-based teaching in science instruction have been made in each of the three reviewed countries, each country demonstrates limitations in the implementation of teacher education that aims at those objectives. None of these countries have rigorous selection criteria for candidates for science teacher education programs, although each has some type of certification or test requirement before entry into the public education system is permitted. The three countries have similar teacher training programs, with instruction programs lasting between 4 and 5 years; programs entail both disciplinary instruction and pedagogical instruction that starts in the first year. Data from the three countries show that a high percentage of instruction in the training programs is devoted to general pedagogy with less instruction time devoted to specific preparation for teaching science. Disciplinary instruction accounts for nearly 50 % of the instruction program among secondary teachers. Training in other subjects such as nature of science, history of science and scientific inquiry is poorly developed. In general, there are few opportunities for research on practicum, as these opportunities tend to occur at the end of the training program. The generation of instruction standards by governments as well as the increase in the number of scholars dedicated to the investigation of science education and the education of science teachers suggests that some of these shortcomings could be remedied in the future.